2016
DOI: 10.1126/science.aai9226
|View full text |Cite
|
Sign up to set email alerts
|

Ten policies for pollinators

Abstract: Earlier this year, the first global thematic assessment from the Intergovernmental Sci-ence-Policy Platform on Biodiversity and Ecosystem Services (IPBES) evaluated the state of knowledge about pollinators and pollination (1,2). It confirmed evidence of large-scale wild pollinator declines in North West Europe and North America, and iden-tified data shortfalls and an urgent need for monitoring elsewhere in the world. With high level political commitments to support pollinators in the US (3), the UK (4) and Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
93
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 13 publications
0
93
0
5
Order By: Relevance
“…provide vital ecosystem services as pollinators of native plant species and agricultural crops (Kearns and Inouye ). However, many bumble bee species are declining across the Northern Hemisphere because of factors that are often inter‐related and include habitat loss and fragmentation (Goulson et al , Koh et al ), agricultural practices (Carvell , Williams and Osborne , Dicks et al ), altered fire regimes (Taylor and Catling ), disease (Cameron et al , Koch and Strange ), and climate change (Potts et al , Kerr et al , Miller‐Struttmann et al ). With declines of bumble bees attributed in part to habitat loss (Goulson et al , Koh et al ), understanding how habitat characteristics influence bumble bee abundance and diversity may help guide land management efforts towards improving habitat for bumble bees and other pollinators (Goulson et al ).…”
mentioning
confidence: 99%
“…provide vital ecosystem services as pollinators of native plant species and agricultural crops (Kearns and Inouye ). However, many bumble bee species are declining across the Northern Hemisphere because of factors that are often inter‐related and include habitat loss and fragmentation (Goulson et al , Koh et al ), agricultural practices (Carvell , Williams and Osborne , Dicks et al ), altered fire regimes (Taylor and Catling ), disease (Cameron et al , Koch and Strange ), and climate change (Potts et al , Kerr et al , Miller‐Struttmann et al ). With declines of bumble bees attributed in part to habitat loss (Goulson et al , Koh et al ), understanding how habitat characteristics influence bumble bee abundance and diversity may help guide land management efforts towards improving habitat for bumble bees and other pollinators (Goulson et al ).…”
mentioning
confidence: 99%
“…The IPBES report suggested that 'ecological intensification' Tittonell 2014) is a key mitigation strategy, and claimed it could transform agriculture to support pollinators, pollination services and food production. Its emphasis on managing beneficial biodiversity to maintain or enhance agricultural productivity is particularly appropriate in the context of global policy objectives to achieve greater food security in a changing world (Dicks et al 2016a;IPBES 2016). Here, we examine the IPBES report's claim in detail, critically evaluating the potential of ecological intensification to mitigate the negative effects of conventional agricultural intensification (industrial management of large-scale monocultures with high chemical inputs) on pollinators and pollination, at landscape (land use) and local (land management) scales.…”
Section: Introductionmentioning
confidence: 99%
“…Many pesticides used in agriculture are harmful, not only to target pests, but also to beneficial arthropods, including pollinating bees 1 . Some pesticides such as acaricides are purposely placed into honey bee colonies for Varroa control.…”
Section: Introductionmentioning
confidence: 99%